2011
DOI: 10.1074/jbc.m110.160390
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-sensing Receptor Decreases Cell Surface Expression of the Inwardly Rectifying K+ Channel Kir4.1

Abstract: The Ca 2؉ -sensing receptor (CaR) regulates salt and water transport in the kidney as demonstrated by the association of gain of function CaR mutations with a Bartter syndrome-like, salt-wasting phenotype, but the precise mechanism for this effect is not fully established. We found previously that the CaR interacts with and inactivates an inwardly rectifying K ؉ channel, Kir4.1, which is expressed in the distal nephron that contributes to the basolateral K ؉ conductance, and in which loss of function mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…8,9 This 40 pS K + channel is a heterotetramer of Kir4.1 and Kir5.1 because the coexpression of Kir4.1/5.1 produced an inwardly rectifying K + channel with the same biophysical properties as the 40 pS K + channel expressed in the basolateral membrane of the native DCT. [10][11][12] The role of Kir4.1 in forming the basolateral 40 pS K + channel of the DCT was convincingly demonstrated by the observation that the disruption of Kcnj10 (Kir.4.1) completely eliminated the 40 pS K + channel. 13 Moreover, the basolateral K + conductance was largely abolished in the early DCT (DCT1) of Kcnj10 2/2 mice, suggesting that Kcnj10 (Kir.4.1) is a major contributor to the basolateral K + conductance in the DCT1.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…8,9 This 40 pS K + channel is a heterotetramer of Kir4.1 and Kir5.1 because the coexpression of Kir4.1/5.1 produced an inwardly rectifying K + channel with the same biophysical properties as the 40 pS K + channel expressed in the basolateral membrane of the native DCT. [10][11][12] The role of Kir4.1 in forming the basolateral 40 pS K + channel of the DCT was convincingly demonstrated by the observation that the disruption of Kcnj10 (Kir.4.1) completely eliminated the 40 pS K + channel. 13 Moreover, the basolateral K + conductance was largely abolished in the early DCT (DCT1) of Kcnj10 2/2 mice, suggesting that Kcnj10 (Kir.4.1) is a major contributor to the basolateral K + conductance in the DCT1.…”
mentioning
confidence: 82%
“…12,19,36 Also, it has been shown that cav-1 interacts directly with c-Src and the interaction domain is within residues 82-101. 37 Therefore, it is possible that cav-1 provides a microenvironment for the interaction between SFK and Kir.4.1.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…K ir 4.1 mutation interferes with basolateral K + recycling, compromising Na-K-ATPase function and generation of the apical membrane potential. Convincing evidence has shown that CaSR, coexpressed in the same region, inhibits cell surface expression of K ir 4.1 [70] via a mechanism dependent on G q and caveolin-1 [70,71] . Reduced Na-KATPase activity due to K ir 4.1 mutations causes a reduced apical NCC activity and apical membrane voltage, the major driving force for Mg 2+ influx [72] .…”
Section: Hnf1b and Pcbd1mentioning
confidence: 99%
“…Reduced Na-KATPase activity due to K ir 4.1 mutations causes a reduced apical NCC activity and apical membrane voltage, the major driving force for Mg 2+ influx [72] . Importantly, CaSR is able to modulate K ir 4.1-mediated potassium extrusion in response to the physiological range of the extracellular Ca 2+ concentration (EC 50 Ca 2+ of 1.0 m M ) [70] . Thus, through CaSR, K ir 4.1 regulates the distal nephron NaCl transport and apical membrane potential physiologically.…”
Section: Hnf1b and Pcbd1mentioning
confidence: 99%